2014
DOI: 10.1177/1368430214558312
|View full text |Cite
|
Sign up to set email alerts
|

Sex as a source of power? Backlash against self-sexualizing women

Abstract: Although women are thought to possess sexual power, they risk social and economic penalties (i.e., backlash; Rudman, 1998) when they self-sexualize (i.e., assert their power; Cahoon & Edmonds, 1989;Glick, Larsen, Johnson, & Branstiter, 2005). Why? Drawing on the status incongruity hypothesis (SIH), which predicts backlash against powerful women because they challenge the gender hierarchy, we expected prejudice against self-sexualizing women to be explained by a dominance penalty rather than a communality defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 53 publications
(75 reference statements)
2
27
0
Order By: Relevance
“…In the present research, we also extended previous findings on backlash and sexual harassment against dominant women (e.g., Infanger, Rudman, & Sczesny, 2014; McLaughlin, Uggen, & Blackstone, 2012; for a meta-analysis, see Williams & Tiedens, 2016). Previous researchers have demonstrated that women’s sexual harassment reflects a hostile reaction to “deviant” women, which is driven by dominance motivations (e.g., Maass et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present research, we also extended previous findings on backlash and sexual harassment against dominant women (e.g., Infanger, Rudman, & Sczesny, 2014; McLaughlin, Uggen, & Blackstone, 2012; for a meta-analysis, see Williams & Tiedens, 2016). Previous researchers have demonstrated that women’s sexual harassment reflects a hostile reaction to “deviant” women, which is driven by dominance motivations (e.g., Maass et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…This possibility is consistent with theorizing that gender inequality is maintained through cooperation between men and women (Jackman, 1994), who actively enforce the existing arrangements (e.g., by endorsing sexist ideologies; Glick & Fiske, 2001). An additional question that may be interesting to test in future research is whether women can actually gain dominance through sexually objectifying themselves, as women’s sexuality may be viewed as a source of social influence (Watkins, Smith, & Aquino, 2013), and there is evidence for a backlash response against self-sexualizing women (because they are perceived as too dominant; Infanger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the report outlined much evidence that sexualization negatively affects women's cognitive functioning, sexuality, attitudes, beliefs, and physical and mental health. Evidence further suggests that although women may feel empowered by self-sexualization, women who self-sexualize sometimes suffer social and economic penalties (Infanger et al, 2014). To this extent, selfsexualization may be inadvertently harmful to women.…”
mentioning
confidence: 99%
“…Compelling evidence demonstrates that people derogate those who act counter to the status quo [50]. Perceptions that women who engage in beautification lack agency may thus function to penalize women who threaten notions of demure and passive femininity through asserting sexual power [43,51]. Perceiving that these women lack agency may also support male dominance by discrediting the agency that some women demonstrate via beautification.…”
Section: The Paradox Of Sexualized Beautification and Female Agencymentioning
confidence: 99%